Towards active utilisation of community forestry: Silvo-institutional model for sustainable forest management in Nepal - Paudel, N. S.; Ojha, H.; Shrestha, K.; Cedamon, E.; Karki, R.; Paudel, G.; Basyal, M.; Nuberg, I.; Dangal, S. (Banko Janakari, 2018)
This paper explains what we term the ‘silvo-institutional model’ for a more productive, sustainable and equitable management of community forests in Nepal. The paper draws on four years of action research in six research sites of Kavre and Lamjung districts, complemented by the review of silviculture-based forest management by Government of Nepal in various parts of the country. The findings indicate that first, early silviculture-based forest management initiatives have failed because they did not adequately consider the policy and institutional dimensions. Second, current initiatives, while looked promising for the active utilisation of community forests, have faced with complex regulatory and institutional barriers. We argue that a new ‘silvoinstitutional model’, which combines technological and institutional dimensions, has a potential to increase the prospect of successful implementation of silviculture-based forest management. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page: 120-129